(untitled) (AYUSHDHARA, 2025)
The history of the surgical instruments’ evolution is a remarkable gradual journey from ancient styles to modern technology-based and engineered precision tools. It would not be wrong if the credit for the first revolutionary change in surgical instruments is primarily attributed to an innovative and pioneering ancient abdominal and cataract surgeon named Sushruta, also known as ’the father of Indian surgery.’ He is credited with innovations in surgical tools in his classic compendium. The tools, designed and described by this master surgeon, mentor, and clinician, are, no matter the birthplace of their provenance, unused due to their innovative functional designs and critical thought processes. Remarkable contributions include the first needle holder, scissors, haemostatic forceps, cesarean section, bone setting, and many kinds of other general and specific surgical instruments. This review is an endeavour to catalogue all the surgical instruments along with their descriptions—and to discuss them in the prevailing modern scientific scenario.